Podróż na zachód. Motywy kolejowe w literackich zapisach depatriacji - Gieba, Kamila (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article is the motif of a train and railway station in the Polish settlement literature. One of the themes of this literature is the journey of the population deported from the eastern borderlands to the so-called Regained Territories. The theme of train travel is analyzed at the following three levels - the dehumanization of a man, the animalization of a train and the desintegration of the space of railway station. The train metaphor not only describes the traumatic journey, but it also organizes the symbolic signification of the so-called Regained Territories as a territory of temporariness and transitivity.
Keywords: literatura osadnicza; Ziemie Odzyskane; pociągi; przestrzeń; dworzec kolejowy; trauma; nie-miejsce; podróż; settlement literature; so-called Regained Territories; trains; train station; space; non-place; travel